1969
DOI: 10.1139/v69-767
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric studies. Part XXV. Methoxy group rotation in anisole and three para-substituted anisoles

Abstract: The dielectric absorption at several microwave frequencies of anisole, p-methylanisole, and p-bromoanisole in the solvent p-xylene, and p-diniethoxybenzene in the solvent cyclohexane has been investigated at 4 to 6 temperatures. Anisole, p-methylanisole, and p-dimethoxybenzene were all found to relax mainly by methoxy group rotation, whereas the relaxation process in p-bromoanisole was very largely niolecular relaxation. In the literature, considerable divergence exists for the analyses of the dielectric data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

1970
1970
1985
1985

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 7 publications
1
3
0
Order By: Relevance
“…The TO values (Table 1) for anisole and p-dimethoxybenzene, especially in the inore viscous solvents, are significantly shorter than those for the rigid bromobenzene. Consequently, the dielectric absorption of the two ethers must, in accord with earlier measurements (8,15,16), contain contributions from an intramolecular relaxation process, i.e. methoxy group rotation.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…The TO values (Table 1) for anisole and p-dimethoxybenzene, especially in the inore viscous solvents, are significantly shorter than those for the rigid bromobenzene. Consequently, the dielectric absorption of the two ethers must, in accord with earlier measurements (8,15,16), contain contributions from an intramolecular relaxation process, i.e. methoxy group rotation.…”
Section: Discussionsupporting
confidence: 76%
“…The errors involved in this type of analysis have been discussed in detail (14). Previous work has shown that the dielectric absorptions of the anisole and pdimethoxybenzene solutions contain contributions from two relaxation processes (8,15,16). In view of the distribution of relaxation times observed for bromobenzene, which has only one relaxation process, however, we have refrained from analyzing the data for the other systems in terms of two discrete relaxation times.…”
Section: Mean Relaxation Times ( T~) mentioning
confidence: 99%
“…These MCSCF calculations were carried out with the iterative natural orbital/valence configuration interaction (Cl) feature of the alis19 system of programs within the molecular orbital basis size listed in Table III. All electrons (15) King, H. F.; Dupuis, M.; Rys, R. QCPE 1980, 13, 403. (16) £toui = -537.32090 au.…”
Section: Calculationsmentioning
confidence: 99%
“…Molecules which liave a methoxy group attached to an aromatic ring have been widely studied by dielectric techniques (1)(2)(3)(4). The n~olecules have bee11 examined either as a pure liquid or as a solute in a dilute solution of a n o n~o l a r solvent and the a b s o r~-tion has been observed in the nlicrowave region.…”
Section: Introductionmentioning
confidence: 99%